Diagnostic Accuracy of Magnetic Resonance Imaging Compared with Arthroscopy in Knee Injuries Among Paramilitary Personnel at a Tertiary Care Center - Thapa, Rossu; Lamichhane, Suman; Bhusal, Amrit; Shrestha, Sailendra Kumar Duwal; Yadav, Sumit; Swar, Avishek; Joshi, Ram Datt (Nepal Journal of Medical Sciences, 2026)
Introduction: Accurate diagnosis of intra-articular knee injuries is essential to guide management and prevent long-term complications. Arthroscopy is the diagnostic gold standard but is invasive, whereas Magnetic Resonance Imaging (MRI) offers a non-invasive alternative. The objective of this study is to assess the diagnostic accuracy of MRI in detecting ligamentous, meniscal, and chondral injuries of the knee by correlating findings with arthroscopy. Methods: Paramilitary personnel with clinically suspected knee injuries who underwent both MRI and arthroscopy were included. MRI findings were compared with arthroscopy, the reference standard, and diagnostic performance indices were calculated. Results: MRI demonstrated high sensitivity and specificity for anterior cruciate ligament, posterior cruciate ligament, and meniscal tears, with relatively lower accuracy for chondral injuries. Conclusions: MRI is a reliable, non-invasive tool for diagnosing major intra-articular knee injuries. Correlation with arthroscopy highlights its strengths and limitations, supporting its role in preoperative evaluation and surgical planning.